2001
DOI: 10.1016/s0764-4469(00)01287-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of parasitoses in a child burial from Adak Island (Central Aleutian Islands, Alaska)

Abstract: Bothriocephalid (Diphyllobothrium pacificum) and Ascarid (Ascaris lumbricoides) eggs have been identified in a sample taken in the abdominal cavity of a child skeleton found in Zeto Point (ADK-011), an archaeological site on Adak Island in the Central Aleutian Islands (Alaska).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…In addition to the findings cited above, BOUCHET et al 17,20 found eggs from genus Diphyllobothrium in samples from Alaska.…”
Section: North and Central Americamentioning
confidence: 72%
“…In addition to the findings cited above, BOUCHET et al 17,20 found eggs from genus Diphyllobothrium in samples from Alaska.…”
Section: North and Central Americamentioning
confidence: 72%
“…The material was placed on a slide that was covered with a coverslip and examined for evidence of parasites and food remains. Twenty slides of each sample were examined at magnification of ×100 and ×400 (Bouchet et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The material was placed on a slide that was covered with a coverslip and examined for evidence of parasites and food remains. Twenty slides of each sample were examined at magnification of ×100 and ×400 (Bouchet et al 2001).For the ELISA tests, the E. histolytica II and the Giardia II assay (TechLab, Blackburg, VA, US) were used. Sample preparation was quite different to provide physicochemical parameter modifications, especially due to formalin (Hould 1984, Exbrayat 2000.…”
mentioning
confidence: 99%
“…Therefore, associated with calibrated dating and well archaeologically and geographically located, skeletons allow obtaining data to associate parasite findings with the human host. Population studies may be approached as far as more skeletons are analyzed.Sediments have been analyzed with paleoparasitological techniques, modified from Stoll technique (Jones 1988, Taek Han et al 2003, spontaneous sedimentations (Faulkner et al 2000, Fernandes et al 2005, sedimentation-flotation (Bouchet 1995, Bouchet et al 1999, 2001, and combining sedimentation and palynological technique (Reinhard et al 1992, Dittmar & Teejen 2003. To understand and interpret correctly parasite finds in sediments of each locality of an archaeological site careful analysis is needed (Reinhard 1988).…”
mentioning
confidence: 99%